Rare Noncoding Mutations Extend the Mutational Spectrum in the PGAP3 Subtype of Hyperphosphatasia with Mental Retardation Syndrome. Issue 8 (19th May 2016) - Knaus, Alexej; Awaya, Tomonari; Helbig, Ingo; Afawi, Zaid; Pendziwiat, Manuela; Abu‐Rachma, Jubran; Thompson, Miles D.; Cole, David E.; Skinner, Steve; Annese, Fran; Canham, Natalie; Schweiger, Michal R.; et al.
Abstract : We describe 8 subjects with Mabry syndrome who have mutations in PGAP3. The non‐coding pathogenic mutations could be identified by targeted enrichment of all gene transcripts of the GPI‐anchor synthesis pathway. The differential analysis of c‐ and gDNA revealed an almost monoallelic expression and pointed to a 3'UTR mutation with a regulatory effect. This finding suggests that PGAP3 is dosage sensitive and a five‐ to ten fold decrease of a functional transcript results in a GPI‐anchor deficiency. ABSTRACT: HPMRS or Mabry syndrome is a heterogeneous glycosylphosphatidylinositol (GPI) anchor deficiency that is caused by an impairment of synthesis or maturation of the GPI‐anchor. The expressivity of the clinical features in HPMRS varies from severe syndromic forms with multiple organ malformations to mild nonsyndromic intellectual disability. In about half of the patients with the clinical diagnosis of HPMRS, pathogenic mutations can be identified in the coding region in one of the six genes, one among them is PGAP3 . In this work, we describe a screening approach with sequence specific baits for transcripts of genes of the GPI pathway that allows the detection of functionally relevant mutations also including introns and the 5′ and 3′ UTR. By this means, we also identified pathogenic noncoding mutations, which increases the diagnostic yield for HPMRS on the basis of intellectual disability and elevated serum alkaline phosphatase. In eight affected individuals from different ethnicities, we found seven novel pathogenic mutations in PGAP3 . Besides five missense mutations, we identified an intronic mutation, c.558‐10G>A, that causes an aberrant splice product and a mutation in the 3′UTR, c.*559C>T, that is associated with substantially lower mRNA levels. We show that our novel screening approach is a useful rapid detection tool for alterations in genes coding for key components of the GPI pathway.